A CO2-switchable amidine monomer: synthesis and characterization. Issue 1 (1st January 2017) - Liu, Hanbin; Yin, Hongyao; Feng, Yujun
Abstract: Smart system employed CO2 gas as new trigger has been attracting enormous attention in recent years, but few monomers that are capable of switching their hydrophobicity/hydrophility upon CO2 stimulation have been reported. A novel CO2 responsive monomer, 4-vinylbenzyl amidine, is designed and synthesized in this work with N, N -dimethylacetamide dimethyl acetal and 4-vinylbenzyl amine that is prepared through the Gabriel reaction. In bi-phase solvent of n -hexane and water, the monomer dissolves in n -hexane first and then transforms into water upon the CO2 treatment, indicating a hydrophobic to hydrophilic transition. This transformation is demonstrated as reversible by monitoring the conductivity variation of its wet dimethyl formamide solution during alternate bubbling/removing CO2 . The protonation of 4-vinylbenzyl amidine upon CO2 treatment is demonstrated by 1 H NMR which also accounts for the dissolubility change. The reversible addition-fragmentation chain-transfer polymerization of this monomer is also performed, finding the reaction only occurs in glacial acetic acid. The reason can be ascribed to the different radical structure produced in different solvent.